MoS2 grown in situ on CdS nanosheets for boosted photocatalytic hydrogen evolution under visible light. (15th January 2022) - Zhang, Kejie; Mou, Zhen; Cao, Shihai; Meng, Tingting; Li, Jiacheng; Ling, Guangjie; Zhang, Xiang; Zhou, Zhiping; Meng, Wei
Abstract: A novel nano-heterojunction photocatalysts of CdS/MoS2 with appropriate interfacial contact was successfully obtained by the facile two-step hydrothermal synthesis. The MoS2 ultrathin layer was well combined with CdS nanosheets and formed the interaction, which facilitated the transfer and separation of charges. The CdS/MoS2 15 wt% possessed much higher H2 evolution photocatalytic performance (35.24 mmol h −1 g −1 ), exhibiting an 85.95 times enhancement as compared to that of pure CdS (0.41 mmol h −1 g −1 ). Moreover, the photochemical stability of CdS/MoS2 heterojunctions was excellent, which showed no significant decrease in activity after four cycles of experiments. The finding provides a novel method to integrate the structure of MoS2 with CdS, which exhibits great potential in solar energy conversion. Graphical abstract: Synopsis: The heterojunction photocatalyst CdS/MoS2 was prepared by a facile two-step hydrothermal synthesis, which has high activity and stability toward photocatalytic hydrogen production. Image 1 Highlights: A novel nano-heterojunction photocatalysts of CdS/MoS2 were successfully synthesized. The interfacial contact between CdS and MoS2 played a key role for charge transfer. CdS/MoS2 15 wt% showed high catalytic activity and stability for hydrogen evolution. The possible mechanism for enhanced photocatalytic activity was proposed.